Hubungan Kelebihan Berat Badan terhadap Tingkat Risiko Diabetes Mellitus Tipe II pada Mahasiswa Kelas Program Khusus Jurusan Keperawatan dan Kebidanan Poltekkes Kemenkes Palangka Raya - Berthiana Berthiana; Mimin Lestari; Dian Ana Mutriqah (Borneo Journal of Medical Laboratory Technology, 2019)
The world is now inhabited by 171 million people with Diabetes Mellitus (DM) and will double, an estimated 366 million by 2030. Obesity is a risk factor for type II DM. From the results of surveys and observations of researchers at the Palangka Raya Polytechnic, it was seen that some special program class students fall into the category of overweight and obese. This research aims to find out the relationship between overweight and the risk level of type II diabetes melitus in class students specialized in nursing and midwifery courses at Palangka Raya Polytechnic. A quantitative study with correlational studies and research design using a cross-sectional approach. There is a significant relationship between overweight to the risk level of type II DM based on the analysis of chi-square test data, obtained p-value = 0.077. There was a relationship between excess body weight based on body mass index on the risk level of type II DM